Soil and vegetation sampling during the early stage of Fukushima Daiichi Nuclear Power Plant accident and the implication for the emergency preparedness for agricultural systems. (November 2020) - Onda, Yuichi; Sweeck, Lieve; Shinano, Takuro; Dercon, Gerd; Yi, A. Lee Zhi; Kato, H.
Abstract: After the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, immediate soil and vegetation sampling were conducted according to the action plan of nuclear emergency monitoring; however, analysing the monitoring dataset was difficult because the sampling protocols were not standardised. In this study, the sampling protocols applied just after the FDNPP accident were reviewed, and the monitoring data were analysed. The detailed protocols and results can provide a sound basis for guidelines of soil and vegetation sampling for nuclear emergency monitoring. The activity concentrations of 137 Cs and 131 I in weed samples measured immediately after the FDNPP accident were related to the air dose rate at 1 m. Consequently, vegetation sampling is recommended when the additional dose rate (above background) is higher than 0.1 μSv/h. To enhance the efficiency of a protective response in the case of a nuclear accident, predetermined sampling points for soil and vegetation sampling should be considered in the preparedness plan for nuclear emergencies. Furthermore, sampling and analytical measurement capacities (time, people, cost) during the early phase after nuclear emergencies need to be considered in the preparedness and action plan, and sampling and measurement exercises are highly recommended. Highlights: The sampling protocols applied just after the FDNPP accident have been reviewed and the protocols for emergency the soil and vegetation sampling were proposed. As a result of Fukushima's outcome, vegetation sampling will be recommended when the additional dose rate (above background) is higher than 0.1 μSv/h. Predetermined sampling points for soil and vegetation sampling and measurement exercises are highly recommended.